Estimating Total Excess Mortality During a Coronavirus Disease 2019 Outbreak in Stockholm, Sweden. (18th October 2020) - Pimenoff, Ville N; Elfström, Miriam; Baussano, Iacopo; Björnstedt, Mikael; Dillner, Joakim
Abstract: Total excess mortality peaked during a coronavirus disease 2019 (COVID-19) outbreak in Stockholm, but 25% of these deaths were not recognized as COVID-19 related nor occurred in hospitals. Estimate of total excess mortality may give a more comprehensive picture of the total disease burden during a COVID-19 outbreak, and may facilitate managing future outbreaks.